Enhancing drainage pipeline inspection advanced integration of six-axis sensor fusion and extended Kalman filter - Meng, Jinheng (Water science and technology : a journal of the International Association on Water Pollution Research, 2025)
© 2025 The Authors This is an Open Access article distributed under the terms of the Creative Commons Attribution Licence (CC BY-ND 4.0), which permits copying and redistribution with no derivatives, provided the original work is properly cited (http://creativecommons.org/licenses/by-nd/4.0/).